2011
DOI: 10.5980/jpnjurol.102.726
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Rectal Migratin of Mesh After TVM (Tension-Free Vaginal Mesh) Operation

Abstract: A 64-year-old woman presented with recto-cutaneous fistula after tension-free vaginal mesh reconstruction using polypropylene mesh for pelvic organ prolapse. Eleven months after the operation, an ulcerative lesion with stools smell secretion developed in the left hip. Magnetic resonance imaging and colonoscopy revealed a migration of the left arm of the mesh and a recto-cutaneous fistula. The patient underwent excision of the infected mesh and rectal wall closure together with transient colostomy. After 8 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“… 10 Bujons et al reported vaginal protrusion of a prolene mesh after cystocele repair. 11 Taoka 12 reported a case of rectal migration of mesh in a 64-year-old woman who presented with a recto-cutaneous fistula 11 months after a tension-free vaginal (TVM) repair; the patient was treated by removal of the infected mesh and closure of the rectal wall defect under cover of a temporary colostomy. By contrast with the troublesome symptoms reported in such patients in the literature, the only presenting complaint of our patient was protrusion of foreign material from the rectum.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Bujons et al reported vaginal protrusion of a prolene mesh after cystocele repair. 11 Taoka 12 reported a case of rectal migration of mesh in a 64-year-old woman who presented with a recto-cutaneous fistula 11 months after a tension-free vaginal (TVM) repair; the patient was treated by removal of the infected mesh and closure of the rectal wall defect under cover of a temporary colostomy. By contrast with the troublesome symptoms reported in such patients in the literature, the only presenting complaint of our patient was protrusion of foreign material from the rectum.…”
Section: Discussionmentioning
confidence: 99%